(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Margaret Eleanor Atwood the ‘Queen Bee’ of Canadian literature focuses on the gender roles and problems of women in Canada. Her concern is with the downtrodden and the victimised women. Her novels end with the self assertion and autonomy of the women characters. Margaret Atwood’s Lady Oracle explores the themes of identity, self-discovery, and the role of women in society. The novel follows the journey of protagonist Joan Foster, a successful author who has been living a double life to escape her past. One of the key motifs in the novel is the idea of trap and escape. Joan feels trapped by her past, her relationships, and societal expectations. She creates a false identity for herself to escape this feeling of confinement. However, she eventually realizes that she cannot escape her past and must confront it in order to move forward.